Aspek Inovasi dan Teknologi Dalam Pengembangan Kawasan Danau Toba di Kabupaten Samosir - Anton Parlindungan Sinaga (Inovasi, 2018)
Lake Toba is one area that belongs to the National Tourism Strategic Area (KSPN) as Government Regulation Number 50 Year 2011 on Master Plan of Tourism Development Year 2010-2025. Samosir regency is one of seven districts in the area of Lake Toba. In the effort to develop Lake Toba as a tourist area there are six issues and problems, namely: conservation of water resources, fisheries and environment, agriculture and plantation, culture, tourism, and infrastructure. This study aims to analyze the types of innovation, technology, and infrastructure needed by Samosir Regency in supporting tourism development. Data collection using interview method with questionnaires distribution in sample population. The study sample consisted of: tourists, local people, business actors, local government and related stakeholders. From the research results obtained for Samosir District needed social innovation, innovation and water treatment technology of Lake Toba, innovation and technology of WWTP, policy innovation and governance, innovation infrastructure (homestay), culinary innovation, ulos weaving product innovation, , beans and onions, water transport innovations, price innovations, cultural heritage management innovations, collaborative coordination innovations, infrastructure innovations, buffalo meat processing innovations and technologies, and innovation of international standard toilets. Keywords: tourism, Lake Toba, Samosir District, innovation